Resistance of Alkali-Activated Slag Concrete to Chloride-Induced Corrosion - Joon Woo Park; Ki Yong Ann; Chang-Geun Cho (Advances in Materials Science and Engineering)
The corrosion resistance of steel in alkali-activated slag (AAS) mortar was evaluated by a monitoring of the galvanic current and half-cell potential with time against a chloride-contaminated environment. For chloride transport, rapid chloride penetration test was performed, and chloride binding capacity of AAS was evaluated at a given chloride. The mortar/paste specimens were manufactured with ground granulated blast-furnace slag, instead of Portland cement, and alkali activators were added in mixing water, including Ca(OH)2, KOH and NaOH, to activate hydration process. As a result, it was found that the corrosion behavior was strongly dependent on the type of alkali activator: the AAS containing the Ca(OH)2 activator was the most passive in monitoring of the galvanic corrosion and half-cell potential, while KOH, and NaOH activators indicated a similar level of corrosion to Portland cement mortar (control). Despite a lower binding of chloride ions in the paste, the AAS had quite a higher resistance to chloride transport in rapid chloride penetration, presumably due to the lower level of capillary pores, which was ensured by the pore distribution of AAS mortar in mercury intrusion porosimetry.